2021
DOI: 10.3390/coatings11070804
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Plus Biopolymer Coating Controls Nitrogen Dynamics of Urea in Soil and Increases Wheat Production

Abstract: The low nitrogen utilization efficiency (NUE) of commercial fertilizers is one of the main hurdles in higher crop production and reduction of fertilizer N losses to the environment. However, interactions between most the macronutrients could have synergistic outcomes that affect crop NUE. The coating of urea with macronutrients and biopolymers may control N release and synergistically impact its crop NUE. In this study, urea was coated with 3% of different polymers, combined with 5% potassium iodide (KI) (i) G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Enhanced efficiency of fertilizers with 50% of total N applied at the booting stage had highly significant association with grain quality that proved split application benefits for chemical qualities of wheat 40 . The findings of previous research also showed that polymer coated controlled release urea increased soil N, P and K availability and such synergistic effects led to higher grain yield, N uptake and its recovery (%) in clay loam soils Nezami et al 41 and proved strong support for the current research findings.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Enhanced efficiency of fertilizers with 50% of total N applied at the booting stage had highly significant association with grain quality that proved split application benefits for chemical qualities of wheat 40 . The findings of previous research also showed that polymer coated controlled release urea increased soil N, P and K availability and such synergistic effects led to higher grain yield, N uptake and its recovery (%) in clay loam soils Nezami et al 41 and proved strong support for the current research findings.…”
Section: Discussionsupporting
confidence: 80%
“…Our results showed that BSCU and SCU showed more crop index % than uncoated and neem coated urea. This might be due to slow release fertilizers balanced the nutrients in soil and more availability in plants rhizosphere 2 , 37 , 41 . The S has acidic properties and neutralized the soil's alkalinity 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed in the present study the highest potassium uptake was recorded in combined Cs-KIO 3 and FA-KIO 3 treatments (T 9 , T 10 , T 13 and T 14 ) in both crops' plants and fruits (Table 1 and 2). The increased uptake of K in the crop might result from the increased availability of K in the soil due to the application of potassium iodate, which contains 18% K (Nezami et al, 2021). Two foliar sprays of KIO 3 along with SA -KIO 3 or Cs-KIO 3 complex increased the potassium uptake compared to the treatments that received one foliar spray.…”
Section: Resultsmentioning
confidence: 99%
“…14 ) enhanced the uptake of nitrogen (61.23 and 78.43 Kg ha -1 ), phosphorous (9.88 and 16.79 Kg ha -1 ), potassium (86.45 and 135.89 Kg ha -1 ),…”
mentioning
confidence: 99%
“…The earlier studies reported 50% N losses as NH 3 volatilization [13], 30% as NO 3 leaching/ runoff [14] and >30% as denitrification [15]. The crop plants utilize only 30-60% of applied-N as urea [14,16] and hence N use efficiency (NUE) of crops varies accordingly [14,16,17]. The low NUE could lead to economic losses to farmers as well as environmental hazard.…”
Section: Introductionmentioning
confidence: 99%